Strategi Pengembangan Usaha Pengrajin Perak yang Terancam Punah di Dusun Bakalan Desa Mojodadi Kecamatan Kemlagi Kabupaten Mojokerto - Sonya Brinda; Selvi Indah Nur Cahyani; Nabilla Aulia Insani; Nanda Apriliani; Aswido Yogameswara; Reny Anda Rista; Savira Zulfa Audina; Aldino Ardiansyah; Avreda Sifa’ul Khasanah; Diah Ayu Sagita Putri; Ristika Febrianti; Roby Ferdian Al-Azhar; Erlangga Wisnu Dewa; Fajar Rizqy Kurniawan; Lilis Eka Nur Farida; M Agung Setiyo Budi; Suryani Kartika Dewi; Fredi Yudha Pratama; Muhammad Rofiqul Hafizah; Danang Nurman Ardiansah; Cyntia Aprilita Gusrinda Putri; Arisky Dwi Wibowo; Mokhammad Syokhibul Musythofa; Egi Fahroji; Achmad Latiful Mubin (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
This journal examines the development strategies of silver craftsmen businesses in Bakalan, Mojodadi Village, Kemlagi District, Mojokerto, facing the risk of extinction. This Region, initially known as a center for silver craftsmen, now confronts serious challenges due to changes in market trends and modernization. The research aims to analyze the factors causing the threat of extinction and formulate appropriate development strategies. The research methods include surveys, interviews, and qualitative data analysis. The results indicate that factors such as changes in consumer preferences, lack of innovation in design, and insufficient marketing and distribution support have significantly impacted the decline in the performance of silver craftsmen in Mojodadi Village.